Vocational education and underskilling : lessons from European skills and jobs surveys - Neuber-Pohl, Caroline [Verfasser]; Russo, Giovanni [Verfasser]; Santangelo, Giulia [Verfasser]; Zigova, Katarina [Verfasser] (My University, 2025)
"Vocational education and training (VET) aims to equip students with a mix of general, occupational, and firm-specific skills — skills that are directly relevant to the 'world of work'. In this paper, we investigate whether workers with a VET background have an advantage in securing jobs that match their skills. We focus on underskilling, a condition in which workers' skills are insufficient to meet the demands of their job. We estimate the association between vocational education and underskilling, using both European Skills and Jobs Surveys (ESJS1 and ESJS2), each providing a unique perspective on skills. Both waves of this survey allow us to construct multiple self-reported measures of underskilling. Using the ESJS1, we find that VET workers perceive, on average, a lower degree of underskilling, compared to those with general education. Examining the patterns behind this effect, we show this different perception is driven by lower underskilling in specialized technical skills and already present earlier in their careers. None of these results are replicated using the ESJS2, likely because underskilling is indirectly measured via skill deficit. However, in both surveys, we find that underskilling measures of VET workers fare better in VET systems that are more closely linked to the labor market." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.2.3.1 Potenziale; G 1.3.3.1 Qualifikationsverwertung; 370; Berufsausbildung; Unterwertige Beschäftigung; Bildungsabschluss; Qualifikationsniveau; Qualifikationsverwertung; Mismatch; Europa